2016
DOI: 10.1016/j.jtcvs.2016.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multistage palliation of infants with functional single ventricle and heterotaxy syndrome

Abstract: The management of infants with heterotaxy and a functional single ventricle remains challenging. First-stage palliation is associated with high operative mortality and increased resource utilization owing to surgical morbidity. Nonetheless, outcomes beyond hospital discharge are comparable to those for patients with other single ventricle anomalies. Efforts to improve survival in those patients should focus on perioperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 37 publications
2
60
2
Order By: Relevance
“…Those outcomes are related to the presence of associated cardiac lesions (TAPVC, common atrioventricular valve regurgitation, pulmonary atresia, and heart block) in addition to the extracardiac lesions that all contribute to increased mortality after single ventricle palliation [5, 6, 11, 14-17, 19, 21, 22]. Interestingly, a recent report from our institution showed that patients with heterotaxy syndrome and right dominant ventricle had a trend to better survival than patients with left dominant ventricle, suggesting again that associated lesions rather than dominant ventricle morphology played a larger role in early outcomes in those patients [22].…”
Section: Commentmentioning
confidence: 99%
“…Those outcomes are related to the presence of associated cardiac lesions (TAPVC, common atrioventricular valve regurgitation, pulmonary atresia, and heart block) in addition to the extracardiac lesions that all contribute to increased mortality after single ventricle palliation [5, 6, 11, 14-17, 19, 21, 22]. Interestingly, a recent report from our institution showed that patients with heterotaxy syndrome and right dominant ventricle had a trend to better survival than patients with left dominant ventricle, suggesting again that associated lesions rather than dominant ventricle morphology played a larger role in early outcomes in those patients [22].…”
Section: Commentmentioning
confidence: 99%
“…Many previous reports have shown that heterotaxy was associated with increased mortality risk following various palliative procedures including BTS, Norwood, or PAB. [6][7][8][9][10]14,15,[24][25][26] A recent Society of Thoracic Surgeons study examining hospital survival of 1,505 patients with heterotaxy who underwent surgery demonstrated that discharge mortality was higher in patients with heterotaxy compared to patients without heterotaxy for every procedure mortality risk category and for different subgroups of patients such as those who underwent BTS or Fontan. 14 Several recent single institution reports of palliation outcomes in patients with heterotaxy demonstrated increased mortality, respiratory complications, and more complicated postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the literature data, with a rather favourable prognosis in case of doubleinlet left ventricle, 10 as opposed to the right-type single ventricle, 11,12 or heterotaxis with complete atrio-ventricular canal defect. 13…”
Section: Discussionmentioning
confidence: 99%